The impact of sleep duration on performance among competitive athletes: A systematic literature review - Kirschen, G. W.; Jones, J J.; Hale, L. (Clinical Journal of Sport Medicine, 2020)
The athletic advantage of sleep, although commonly touted by coaches, trainers, and sports physicians, is still unclear and likely varies by sport, athletic performance metric, and length of sufficient or insufficient sleep. Although recent literature reviews have highlighted circadian and nutritional factors that influence different aspects of athletic performance, a systematic summary of the effects of sleep duration and sleep quality on performance among competitive athletes is lacking. Here we systematically review the relationship between sleep duration and sleep quality and objective athletic performance among competitive athletes across 19 studies representing 12 sports. Taken holistically, we find that the sports requiring speed, tactical strategy, and technical skill are most sensitive to sleep duration manipulations. Furthermore, longer-term sleep manipulations are more likely than acute sleep manipulations (whether deprivation or extension) to affect athletic performance. Thus, the importance of sleep for competitive athletes to achieve high performance is dependent on the demands of the sport as well as the length of sleep interventions. In light of the limited number of studies investigating sleep quality and performance, the potential relevance of subjective sleep quality remains an interesting question for future work.